In vitro evaluation of five rapid antigen detection tests for group A beta-haemolytic streptococcal sore throat infections. - Lasseter, G; McNulty, C; Richard Hobbs, F; Mant, D; Little, P (2009)
BACKGROUND: Using accurate and easy to use rapid antigen detection tests (RADTs) to identify group A beta-haemolytic Streptococci (GABHS) sore throat infections could reduce unnecessary antibiotic prescribing and antimicrobial resistance. Although there is no international consensus on the use of RADTs, these kits have been widely adopted in Finland, France and the USA. Yet in the UK, the Clinical Knowledge Summaries, that provide the main online guidance for GPs, discourage RADTs use, citing their poor sensitivity and inability to impact on prescribing decisions in acute sore throat infections. OBJECTIVE: The purpose of this study was to evaluate the ease of use and in vitro accuracy (sensitivity and specificity) of the five most commonly used RADTs in Europe (OSOM Ultra, Quickvue Dipstick, Streptatest, Clearview Exact Strep A and IMI Test Pack). METHODS: To ensure the RADTs were evaluated objectively, a standardized in vitro method using known concentrations of GABHS was used to remove the inherent biases associated with clinical studies. RESULTS: The IMI Test Pack was the easiest RADT to use overall. The ability to detect all positive GABHS (sensitivity) varied considerably between kits from 95% [95% confidence interval (CI): 88-98%], for the IMI Test Pack and OSOM, to 62% (95% CI: 51-72%) for Clearview, at the highest GABHS concentration. None of the RADTs gave any false-positive results with commensal flora-they were 100% specific. CONCLUSIONS: The IMI Test Pack is most suitable for use in primary care, as it had high sensitivity, high specificity and was easy to use.